2018
DOI: 10.1002/er.4138
|View full text |Cite
|
Sign up to set email alerts
|

Proposition of a critical design direct normal irradiance for solar thermal power plant

Abstract: Summary An appropriate design of solar thermal power plant (STPP) is important before construction. This present study attempted to deal with some fundamental questions in design of STPP. What is the relationship between the optimal design direct normal irradiance (DNI) and weather conditions? What is the optimal solar multiple for a STPP at a specific weather condition? How does the thermal energy storage (TES) affect the electricity output of STPP, and how does dispatch fraction affect the usage of stored th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Solar heat power generation stations usually adopt heat storage measures so as to solve solar energy instability problem. Therefore, in the solar thermal power generation unit, the heat storage technology plays an essential part, and capacity of its efficient heat storage as well as release is particularly important [5]. The solar thermal power generation unit can store the surplus heat by melting latent heat through solid-liquid phase change by adopting phase change heat storage technology [6].…”
Section: Introductionmentioning
confidence: 99%
“…Solar heat power generation stations usually adopt heat storage measures so as to solve solar energy instability problem. Therefore, in the solar thermal power generation unit, the heat storage technology plays an essential part, and capacity of its efficient heat storage as well as release is particularly important [5]. The solar thermal power generation unit can store the surplus heat by melting latent heat through solid-liquid phase change by adopting phase change heat storage technology [6].…”
Section: Introductionmentioning
confidence: 99%
“…Insulation thickness was also found to only slightly prevent heat loss from the thermal storage tanks after the first 5 cm. Liu et al designed a model which used to analyze the effect of various factors like solar multiple, design direct normal irradiance (DNI), TES size, and dispatch fraction on solar energy usage efficiency. They found that critical design DNI can be reduced by increasing storage size and the dispatch fraction.…”
Section: Introductionmentioning
confidence: 99%